Linkage and association studies of single-nucleotide polymorphism-tagged tumor necrosis factor haplotypes in juvenile oligoarthritis. - Zeggini, E; Thomson, W; Kwiatkowski, D; Richardson, A; Ollier, W; Donn, R (2002)
OBJECTIVE: The presence of increased levels of tumor necrosis factor (TNF) in serum and synovial fluid of patients and the encouraging outcome of anti-TNF therapy have implicated TNFalpha in the etiopathogenesis of juvenile oligoarthritis. Although the locus is polymorphic, no study has investigated all TNF single-nucleotide polymorphisms (SNPs) with respect to disease. The aim of this study was to examine the association of multiple TNF SNPs with juvenile oligoarthritis and to construct and analyze SNP-tagged TNF haplotypes. METHODS: A total of 144 simplex families consisting of parent and affected child, as well as 88 healthy, unrelated control subjects were available for study. In these individuals, 9 polymorphic positions of TNF were typed by a high-throughput genotyping method based on the SNaPshot assay. The chi-square and extended transmission disequilibrium tests were used to test for association and linkage, respectively. Odds ratios (ORs) with 95% confidence intervals (95% CIs) were also calculated. Haplotype-tagging SNPs (htSNPs) for the locus were identified by ordering the haplotypes according to their frequencies. RESULTS: The study detected association of several TNF SNPs and established linkage of the locus to juvenile oligoarthritis. The most significant association observed was between the intronic +851 TNF SNP and the persistent oligoarthritis subgroup (OR 3.86, 95% CI 1.6-9.2). Haplotype data mining showed that only 4 of the 9 SNPs need to be typed in order to capture the most frequent TNF haplotypes. CONCLUSION: The TNF locus is linked and associated with juvenile oligoarthritis. Information on the htSNPs can be useful in genetic studies of diseases in which TNF may be of relevance.